The path from social origins to top jobs: social reproduction via education1. (3rd October 2017) - Sullivan, Alice; Parsons, Samantha; Green, Francis; Wiggins, Richard D.; Ploubidis, George
Abstract: This paper provides a comprehensive account of the way in which cognitive and educational attainment mediate the link between social origins and elite social class destinations in mid‐life. Using the 1970 British Cohort Study (BCS70), we assess the roles of a range of pathways through which educational advantage may lead to occupational attainment: cognitive development; private and selective secondary schools; school level qualifications; and higher education, including institution and field of study. Whereas past research has shown a residual direct effect of social origins on class destinations, we find that, once a sufficiently detailed picture of educational attainment is taken into account, education fully explains the link between social origins and top social class destinations. In contrast, the gap between men and women in achieving top social class positions is in no part accounted for by education.